2016
DOI: 10.1021/acschembio.6b00939
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Two Late-Stage Enzymes Involved in Fosfomycin Biosynthesis in Pseudomonads

Abstract: The broad-spectrum phosphonate antibiotic fosfomycin is currently in use for clinical treatment of infections caused by both Gram-positive and Gram-negative uropathogens. The antibiotic is biosynthesized by various streptomycetes, as well as by pseudomonads. Notably, the biosynthetic strategies used by the two genera share only two steps: the first step in which the primary metabolite phosphoenolpyruvate (PEP) is converted to phosphonopyruvate (PnPy), and the terminal step in which 2-hydroxypropylphosphonate (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 43 publications
0
19
0
Order By: Relevance
“…11 In the last step, the epoxidase Fom4 converts exclusively the S enantiomer of 2-HPP to fosfomycin. 6,17,18 The stereospecificity of this reaction has been demonstrated both by feeding stereospecifically 2 H-labeled 2-HPP to fosfomycin-producing Streptomyces fradiae and by in vitro enzyme assays, 6,1820 which have also shown that Fom4 converts ( R )-2-HPP to 2-oxopropylphosphonate (2-OPP). 18,20…”
mentioning
confidence: 99%
“…11 In the last step, the epoxidase Fom4 converts exclusively the S enantiomer of 2-HPP to fosfomycin. 6,17,18 The stereospecificity of this reaction has been demonstrated both by feeding stereospecifically 2 H-labeled 2-HPP to fosfomycin-producing Streptomyces fradiae and by in vitro enzyme assays, 6,1820 which have also shown that Fom4 converts ( R )-2-HPP to 2-oxopropylphosphonate (2-OPP). 18,20…”
mentioning
confidence: 99%
“…1013 In the final step of fosfomycin biosynthesis in Streptomyces, ( S )-HPP is converted to fosfomycin by the nonheme iron peroxidase Fom4, which is also referred to as HppE. 1416…”
mentioning
confidence: 99%
“…Interestingly, 2-hydroxypropylphosphonic acid epoxidase (HppE) implements partially similar biochemical mechanics as PhnZ. An enzyme from Streptomyces wedmorensis cells is the most investigated and located basally ( Figure 21 ) though other homologs, for example, evolutionally novel enzyme from Pseudomonas syringae (26% identity), are also issued [ 100 ]. HppE forms homotetramer and naturally participates in fosfomycin (i.e., natural antibiotic with phosphonate moiety) biosynthesis [ 86 ].…”
Section: Enzymes Acting On Phosphonatesmentioning
confidence: 99%